2021
DOI: 10.1021/acs.organomet.1c00454
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Alkyne Carboamination via an Isolable Iron Imide Complex

Abstract: Transition metal imide-mediated C–N bond formation is a powerful strategy for the introduction of nitrogen into organic compounds. We have discovered that the reaction of N-mesityl­(β-diketiminato)­iron imide complex tBuLFeNMes ( tBuL = 3,5-bis­(2,6-diisopropylphenylimino)-2,2,6,6-tetramethylheptyl and Mes = 2,4,6-trimethylphenyl) with a terminal alkyne substrate gives a β-alkynyl enamine product by a novel alkyne carboamination process. Stoichiometric experiments revealed a catalyst deactivation pathway invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…This distance is similar to those of the four-coordinate Fe(III) imidyl complexes reported by Betley, ( Ar L)FeCl(]NC 6 H 4p-t Bu) (1.768(2) Å) 39 and ( tBu L)FeCl(]NDipp) (1.768(4) Å), 40 and that of the imido-Fe 4 S 4 cluster complex reported by Suess and co-workers, (IMes) 3 Fe 4 S 4 ]NDipp (1.763(2) Å, IMes ¼ 1,3bis(2,4,6-trimethylphenyl)imidazol-2-ylidene). 58 In addition, the short N(3)-C (33) distance and the elongation of the C(33)-C (34) and C(33)-C(38) distances of the mesityl ring (Fig. 2) indicated radical delocalization.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This distance is similar to those of the four-coordinate Fe(III) imidyl complexes reported by Betley, ( Ar L)FeCl(]NC 6 H 4p-t Bu) (1.768(2) Å) 39 and ( tBu L)FeCl(]NDipp) (1.768(4) Å), 40 and that of the imido-Fe 4 S 4 cluster complex reported by Suess and co-workers, (IMes) 3 Fe 4 S 4 ]NDipp (1.763(2) Å, IMes ¼ 1,3bis(2,4,6-trimethylphenyl)imidazol-2-ylidene). 58 In addition, the short N(3)-C (33) distance and the elongation of the C(33)-C (34) and C(33)-C(38) distances of the mesityl ring (Fig. 2) indicated radical delocalization.…”
Section: Resultsmentioning
confidence: 96%
“…4,5 In addition, high-spin states are rare among these compounds, with most of them being in low- and intermediate-spin states. 3,6–35 Many of the terminal imido complexes of Fe characterized to date contain traditional closed-shell imido ligands, represented as NR 2− (R = alkyl, aryl). 3 It has been shown that inducing a weak ligand field around the metal center enables the isolation of the open-shell imidyl ligand with a radical on its N, represented as ˙NR − .…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the iron-catalyzed coupling of organic azides with aryl acetylenes to afford β-alkynyl enamines 1 (Scheme 2, top). 40 Our mechanistic evaluation of this carboamination process led us to consider two pathways for the initial interaction of the alkyne substrate and the proposed iron imide intermediate (Scheme 2, bottom). In pathway A, the basic imide nitrogen 41 deprotonates the relatively acidic terminal proton of the aryl acetylene to give an alkynyl amide complex.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We recently reported the isolation and characterization of the first monometallic iron azametallacyclobutene complex (1; Scheme 1b) 15 that was discovered during our investigation into the mechanism of iron-catalyzed alkyne carboamination. 16 Details from the molecular structure of 1 hinted at a delocalized π system within the metallacycle (vide infra). Herein we report our investigation of the electronic structure of 1 as well as our exploration into its reactivity prompted by observations from this computational study.…”
Section: ■ Introductionmentioning
confidence: 99%